Rational Combinations of Targeted Therapy and Immune Checkpoint Inhibitors in Head and Neck Cancers - Chai, Annie Wai Yeeng; Yee, Pei San; Cheong, Sok Ching (Frontiers in Oncology, 2022)
Immunotherapy, especially the immune checkpoint inhibitors (ICIs) such as the pembrolizumab and nivolumab have contributed to significant improvements in treatment outcomes and survival of head and neck cancer (HNC) patients. Still, only a subset of patients benefits from ICIs and hence the race is on to identify combination therapies that could improve response rates. Increasingly, genetic alterations that occur within cancer cells have been shown to modulate the tumor microenvironment resulting in immune evasion, and these have led to the emergence of trials that rationalize a combination of targeted therapy with immunotherapy. In this review, we aim to provide an overview of the biological rationale and current strategies of combining targeted therapy with the approved ICIs in HNC. We summarize the ongoing combinatorial clinical trials and discuss emerging immunomodulatory targets. We also discuss the challenges and gaps that have yet to be addressed, as well as future perspectives in combining these different drug classes.